Directions of Perfection of State Regulation of Industrial Development - N. M. Abdikeev; Yu. S. Bogachev; E. L. Moreva (Учёт. Анализ. Аудит)
The need for strengthening practical orientation of the strategies and concepts for industrial development that have been recently put forward in our country makes us turn to searching for a solution to the problems of the control of the transition of the secondary sector to the new technological mode in the conditions of limited access to international markets, finance and technologies, problems of institution-building and other unfavorable factors impeding the formation of a modern competitive economy. This article is devoted to the identification and justification of specific ways to improve state regulation of industrial development. In order to achieve this goal, both general scientific and private economic methods were used, including analysis and synthesis, systematic approach, statistical material and other research tools were widely used. Their use while examining the state of industrial structure and government regulation of its development has allowed to identify the causes of low efficiency of management of industrial development and formulate the proposals for its improvement. Therefore, there the directions of the system structuring of political and economic course were particularized, and also the institutional securing mechanisms as well as the principles to ensure the implementation of these mechanisms were defined. In practice this toolkit was used to analyze the status or condition and the proposals for the course on strategic import substitution, as well as the regulation of the development of production and technological base of industrial complexes. Consistent application of the identified principles and tools in the study regarding other policies of industrial development entails further elaboration of the raised issues on accounting in the system of industrial development stimulation, changing the values of different factors of increasing competitiveness, lowering production costs that occur under the conditions of transition to the 6th technological mode, including the priorities for lower production costs, the causes of the deficit human capital and the conditions for its overcoming, modernization of methods of supporting industrial development, the relationship of internal and external factors of industrial development.